Digital Nomad Influence on Malay Work Ethics: Exploring Cultural Dynamics - Fahmi, Rizqi Anfanni; Rusli, Ris'an; Sani, Amilda (SCAD Independent, 2024)
The trend of digital nomadism has increased for several years, but limited studies examined digital nomadism from a work ethic view. This study explores the possibility of the Malays being digital nomads using Weber’s Work Ethic and Cultural Adaptationist approach. This study used a qualitative approach with a library research design. A qualitative study was conducted by scrutinizing literature related to digital nomads and Malays’ work ethic. Two primary keywords for obtaining data were “Digital Nomads” and “Malay Work Ethic”. After searching for these keywords, 127 articles, books, and reports were received and sorted again according to research purposes. The selected sources were subjected to thematic analysis to identify patterns, concepts, relations, and meanings gathered from the data. The results show that the Malays will potentially join the digital nomadism trend in the future, but they will preserve Islamic values as their work ethic principles. Digital nomads in the Malay region should adapt to local values to be accepted in local communities. This study contributes to the Malay World study in response to the globalization of the workplace.